RANCANG BANGUN SISTEM INFORMASI PENDATAAN ASET SEKOLAH DASAR BERBASIS WEB DENGAN QR CODE PADA DINAS PENDIDIKAN KOTA SURAKARTA MENGGUNAKAN METODE R&D - Nabilla Putri Sari Fatikhah; Aprilisa Arum Sari; Agustina Purwatiningsih (Simtek : jurnal sistem informasi dan teknik komputer, 2026)
The process of recording elementary school assets at the Surakarta City Education Office remains conventional, making it prone to errors in data entry, reporting delays, difficulties in data compilation, and inefficient asset inspections. This study was conducted to develop a web-based asset data management system integrated with QR codes to facilitate the identification, recording, and reporting of assets. The system is designed so that each asset has a unique code that can be scanned to display information quickly and accurately, while schools can upload asset data along with proof of purchase remotely. The results of the study show that the developed system supports centralized data collection, speeds up reporting, facilitates asset verification, and organizes documents more effectively. Thus, the system improves the performance, accuracy, and transparency of asset management in elementary schools.